Age Threshold for Ischemic Stroke Risk in Atrial Fibrillation: Cohort Data Covering the Entire Korean Population. Issue 8 (August 2018) - Kim, Tae-Hoon; Yang, Pil-Sung; Yu, Hee Tae; Jang, Eunsun; Uhm, Jae-Sun; Kim, Jong-Youn; Pak, Hui-Nam; Lee, Moon-Hyoung; Joung, Boyoung; Lip, Gregory Y.H.
Abstract : Background and Purpose—: Although older age is one of the most important risk factor for stroke in atrial fibrillation (AF), the appropriate age threshold (eg, CHA2 DS2 -VASc score [congestive heart failure, hypertension, age ≥75 years (doubled), diabetes mellitus, prior stroke or transient ischemic attack (doubled), vascular disease, age 65–74 years, female], 1 point for age 65–74 years, 2 points for age ≥75 years) for increased risk is controversial because actual age thresholds may differ between countries and ethnic groups. We investigated the age threshold for ischemic stroke risk among Asian AF patients. Methods—: Using National Health Insurance Service database, including 426 650 oral anticoagulant–naive nonvalvular AF patients from 2005 to 2015, with ⩽2 nongender-related CHA2 DS2 -VASc risk scores (CHA2 DS2 -VASc score 0–2 in males, 1–3 in females), we assessed the risk of ischemic stroke in AF patients according to the age. Results—: Patients who fulfill the age risk criterion (age, 65–74 years) without other risk factors showed a significantly higher risk of stroke (4.76 per 100 person-years [100PY]; adjusted hazard ratio, 2.25; 95% confidence interval [CI], 2.17–2.36) compared with patients with 1 risk score other than age (1.87/100PY). Patients aged 55 to 59 years with no risk factors showed similar risk of stroke (1.94/100PY; adjusted hazard ratio, 0.95; 95% confidence interval, 0.90–1.00) than patients with 1 risk score (2.06/100PY). Patients aged 65 to 69 years and no other risk factors had similar stroke risk (4.08/100PY; adjusted hazard ratio, 0.93; 95% confidence interval, 0.90–0.97) than patients with 2 nongender-related risk scores (4.42/100PY). Conclusions—: Older age is the most important predictor of ischemic stroke in AF, particularly for patients with low to intermediate risk of stroke. These nationwide data suggest lowering the current age threshold (age, ≥65 years) in the CHA2 DS2 -VASc score to age ≥55 years might be appropriate among Asian patients with AF. Abstract : Supplemental Digital Content is available in the text.